Circadian rhythms of proliferation events in two mouse carcinomas - Garcia, Marcela (2015)
We studied the index of DNA synthesis (DNAs) of two cellular carcinomas: the hepatocellular ES12a and the mammary TN60 of mice, throughout one circadian cycle. In the results, we observed that both tumors have circadian rhythms (CRs), but the peaks of DNAs vary. Besides, the mean of DNAs along 24 h shows significative differences, the TN60 has higher values than the ES12a. These observed CR in the DNAs index in both carcinomas mean that, at least in partly, the proliferation of cancer cells can be regulated by endocrine factor as it normally occurs in ordinary cells. The big problem we can find for the chronopharmacology is that it is impossible to know in advance the rate of proliferation of each tumor.